Design of two-dimensional perovskite solar cells with superior efficiency and stability (2021)
ABSTRACT : Pervskite solar cells have attracted extensive attention from researchers worldwide due to their rapid development and efficiency. Nevertheless, stability is still an issue that limits the advance of this technology. In this work, we present the fabrication and characterization of two-dimensional perovskites of the Ruddlesden-Popper’s family (A)2(MA)n−1PbnI3n+1 (three different A-site large cations were investigated: A=n-propylammonium, t-Butylammonium or Benzylammonium). The modulation of the large organic cations increased the band gap of the materials and improved moisture and thermal stability, making it possible to fabricate PSCs. Even though the organic interlayers intrinsically reduce the transport properties of the devices and therefore lower currents are obtained in the layered systems, a remarkable efficiency of 10.35% was obtained for (BUA)2(MA)2Pb3I10, with superior stability, and therefore, it was possible to retain 68% of its initial value after 1700 h for devices without encapsulation.